Bispecific antibodies and chimeric antigen receptor (CAR) T-cell therapy for indolent lymphoma (Canadian Hematology Today, 2023)
Classic follicular (FL) and marginal zone (MZL) lymphomas are the primary indolent non-Hodgkin lymphomas (iNHL). Once first-line therapy is initiated, the majority of patients eventually experience treatment failure and face progressively shorter disease-free periods following subsequent lines of conventional chemotherapy. Patients with progressive disease within 24 months of first-line therapy (POD24) represent a significant unmet need. The five-year overall survival (OS) for patients with FL and POD24 is only 50% vs 90% for those without POD24. The three-year OS for patients with MZL is 53% and 95% respectively.